"Did You Ever Fight Back?" Jurors' Questions to Children Testifying in Criminal Trials About Alleged Sexual Abuse. (August 2020) - St. George, Suzanne; Garcia-Johnson, Anastacia; Denne, Emily; Stolzenberg, Stacia N.
The current study examined jurors' questions to children in criminal trials assessing children's allegations of sexual abuse, demonstrating a new avenue for studying how jurors think about, respond to, and assess evidence. We used qualitative content analysis to examine jurors' questions to 134, 5- to 17-year-olds alleging sexual abuse in criminal trial testimonies. Five themes emerged: abuse interactions, contextual details of abuse, children's reactions to abuse, children's (delayed) disclosure, and case background details. Jurors often ask about abuse dynamics, the context surrounding abuse, and children's disclosure processes, reflecting common misconceptions about child sexual abuse (CSA), such as whether it is credible to delay disclosure or maintain contact with an alleged perpetrator. This study improves our understanding of how jurors understand and evaluate children's reports of alleged CSA, suggesting that jurors may struggle to understand children's reluctance.